Digitalized Cross-Border Telework: Challenge to Workplace Democracy - Yenisey, Kübra DoĞAN (Kluwer Law International, 2026)
The rapid expansion of digitalized cross-border telework challenges the traditional foundations of workplace democracy by complicating the exercise of workers’ information and consultation (I&C) rights. These rights, although fundamental within the European social model and recognized under Article 27 of the EU Charter of Fundamental Rights, are not universally protected or implemented, particularly outside Europe. This paper examines the multifaceted challenges posed by cross-border telework to the realization of I&C rights. First, it explores the tensions between their fundamental nature and the diversity of national legal mechanisms ensuring their application. Second, it analyses how cross-border telework extends these challenges into private international law, creating uncertainty over applicable laws and competent representation units. Through comparative legal analysis, the paper argues that traditional, location-based models of representation are increasingly inadequate in the digital context. It proposes a conceptual reorientation from the spatial question of where representation occurs to the personal question of which employees fall within its scope. Such a shift, it contends, would not only strengthen the effectiveness of I&C rights in cross-border contexts but also reinforce their democratic character, ensuring that employees remain meaningfully represented within evolving forms of work organization. © 2026 Kluwer Law International BV, The Netherlands [pre-publication]
Keywords: cross-border telework; digitalization; EU Law; information and consultation rights; representation unit; workplace democracy